2023
DOI: 10.1021/jasms.2c00259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ambient Vapors on Spectra of 4-Nitroaniline Recorded under Atmospheric Solids Analysis Probe (ASAP) Mass Spectrometric Conditions

Abstract: Thermally desorbed 4-nitroaniline (4-NA), upon atmospheric pressure chemical ionization (APCI), generates gaseous ions for its protonated species. The APCI mass spectrum recorded under mild in-source ion-activating conditions from 4-NA showed a peak at m/z 139, whereas that acquired under high ion-activating conditions showed two additional peaks at m/z 122 ( • OH loss) and 92 ( • NO loss). The spectrum changed instantaneously when acetonitrile vapor was introduced to the source. In the new spectrum, both m/z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Several studies , have focused on the final stages of desolvation under ESI where, following the expulsion of the microsolvated ion from a charged droplet, the stability of the protonation site for the last few solvent molecules ultimately dictates the protomer population. Other studies provide evidence that at atmospheric pressure, the controlled delivery of selected solvent vapor can affect the final protomer ratios, which may point toward additional processes. ,, Even in these small cluster ions, at these final stages of desolvation, there are complex kinetics leaving some ambiguity to the mechanism(s) at play.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies , have focused on the final stages of desolvation under ESI where, following the expulsion of the microsolvated ion from a charged droplet, the stability of the protonation site for the last few solvent molecules ultimately dictates the protomer population. Other studies provide evidence that at atmospheric pressure, the controlled delivery of selected solvent vapor can affect the final protomer ratios, which may point toward additional processes. ,, Even in these small cluster ions, at these final stages of desolvation, there are complex kinetics leaving some ambiguity to the mechanism(s) at play.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with cryogenic ion mobility studies that derived a collisional cross section consistent with the bridged [ p ABA + H] + (H 2 O) 6 (Grotthuss) intermediate. Solvent-bound heterodimers have also been implicated as an important intermediate in protomer formation. ,, A recent study has shown that for para -nitroaniline, the nitro and amino protomer ratio was governed by the formation of either water or acetonitrile bound dimers in the atmospheric pressure ion source. Fragmenting the water dimer produced the nitro protomer, and the acetonitrile dimer produced the amino protomer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,22 Many mechanisms have been proposed to rationalize the observed transformations: (i) proton transfer from one site to the other via a solvent vapor bridge (Grotthuss mechanism); 23 (ii) a single solvent vapor molecule acting as a carrier vehicle to transport the proton within the ion−dipole complex; 24 and (iii) formation and dissociation of functional-group-specific proton-bound heterodimers created with solvent vapors present in the ion source. 25 Although a large body of research data support the Grotthuss-type mechanism, 8,12,26,27 the involvement of solvent vapor molecules in the mediation process, whether it is a single molecule or multiple molecules, appears to rely on the nature of the vapor molecules and the pressure exerted on the interacting entities. For example, under relatively low pressure and short ion storage ion-trap conditions, the number of solvent vapor molecules available is insufficient to facilitate the Grotthuss mechanism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many mechanisms have been proposed to rationalize the observed transformations: (i) proton transfer from one site to the other via a solvent vapor bridge (Grotthuss mechanism); (ii) a single solvent vapor molecule acting as a carrier vehicle to transport the proton within the ion–dipole complex; and (iii) formation and dissociation of functional-group-specific proton-bound heterodimers created with solvent vapors present in the ion source …”
Section: Introductionmentioning
confidence: 99%